Ҳалима Худойбердиева шеъриятида қўлланган лафзий санъатларда лексик бирликларнинг бадиий-эстетик вазифалари (SCIENCE and SOCIETY, 2022)
In this article, a lexical analysis of the verbal arts used in the portry of the poet Halima Khudoiberdiyeva, a poet is given with a beau- tiful outlook and sharp comprehension, scientifically based conclusions.